Thermodynamics and kinetics studies of Phenol adsorption on to Anchote peel activated carbon adsorbent - Shifera, Leta (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Thermodynamic and kinetics (pseudo first, pseudo second) of phenol adsorption were investigated. Anchote peel (coconia Abysinica peel) was carbonized and activated by treating with KOH solution followed by heating in an electrical furnace at 800 for 2 hrs. Kinetic studies of the data showed that the adsorption follows the pseudo-second-order kinetic model. Thermodynamic parameters showed that adsorption on the surface of APAC was feasible, spontaneous in nature, and exothermic. The equilibrium data better fitted the Freundlich isotherm model. Maximum adsorption efficiencies of Phenol were 97% at optimum pH 6 and optimum contact time 210 min., adsorbent dose 0.25 g and initial conc. 0.025 mg/l respectively. Maximum adsorption capacity of APAC was observed to 43.75 mg/g of Phenol at 25 and 5 mg/L. Key words: